Pakistan - "Nayak, Pandav (ed.)" (New Delhi, 1984)
The theme of Paktman: Society Pollie is on and around the isaves pertaining to the star structure of Pakistan. As such, it is spread over the issues relating to: (i) the role of Islam and the origin of Pakistan; (ii) structural problems relating to the Constitution, military, ethnic movements and politici conomy of the State; (iii) processual aspects covering PPPdership, federalism, etc.; and (iv) external environment such as US aid and its implications and Pakistan's relationship with India, Afghanistan and the countries of the Muslim World.
Keywords: Pakistan politics and government